Evaluation of molecular typing for national surveillance of invasive clinical Haemophilus influenzae isolates from Denmark - Slotved, Hans-Christian; Johannesen, Thor Bech; Stegger, Marc; Fuursted, Kurt (Frontiers in Microbiology, 2022)
Haemophilus influenzae is a gram-negative coccobacillus known to cause respiratory and invasive infections. It can possess a polysaccharide capsule that can be categorized into six different serotypes (i.e., Hia, Hib, Hic, Hid, Hie, and Hif) and non-encapsulated strains that are defined as non-typeable. Furthermore, H. influenzae can be characterized into eight biotypes (I–VIII). Traditionally, isolates have been serotyped and biotyped using phenotypic methods; however, these methods are not always reliable. In this study, we evaluate the use of whole-genome sequencing (WGS) for national surveillance and characterization of clinical Danish H. influenzae isolates. In Denmark, all clinical invasive isolates between 2014 and 2021 have been serotyped using a traditional phenotypic latex agglutination test as well as in silico serotyped using the in silico programs “hinfluenzae_capsule_characterization” and “hicap” to compare the subsequent serotypes. Moreover, isolates were also biotyped using a phenotypic enzyme test and the genomic data for the detection of the genes encoding ornithine, tryptophan, and urease. The results showed a 99–100% concordance between the two genotypic approaches and the phenotypic serotyping, respectively. The biotyping showed a 95% concordance between genotyping and phenotyping. In conclusion, our results show that in a clinical surveillance setting, in silico serotyping and WGS-based biotyping are a robust and reliable approach for typing clinical H. influenzae isolates.